The effect of gender, work stress and compliance pressure on audit judgement, with task complexity as a moderation variable - YUNI PRATIWI GAZALI; ARIFUDDIN; AMIRUDDIN (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to examine and analyze the effect of gender, work stress, and obedience pressure on audit judgment, with task complexity as a moderating variable. The population in this study were 112 auditors who worked at the Office of the Financial and Development Supervisory Agency. The type of sample used is purposive sampling because the sample selection is based on predetermined criteria. The sample in this study was 106 auditors. Data analysis used descriptive statistical analysis, data quality test, classic assumption test, and research hypothesis test. The results showed (1) gender has a positive effect on audit judgment, (2) work stress has a positive effect on audit judgment, (3) obedience pressure has a negative effect on audit judgment, (4) task complexity moderates (strengthens) gender on audit judgment, (5) task complexity moderates (strengthens) work stress on audit judgment, and (6) task complexity moderates (weakens) obedience pressure on audit judgment.